P-72 NOT hiding who I am. Supporting LGBT+ staff in hospices. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Powell, Martin
Abstract : Background: In the United Kingdom there is increasing interest in how LGBT patients access and experience healthcare, including end of life and palliative care. We know there is higher prevalence of life-limiting disease in LGBT people, attributed to lifestyle factors and fear of homophobia, discrimination and marginalisation (Marie Curie, 2016). Much less attention is paid to LGBT staff, and of interest to us those working in hospices, and their support needs. A quarter of LGBT health and social care staff report experiencing bullying, discrimination or other forms of poorer treatment due to their sexual orientation (Quaile, 2018). When staff are healthy and happy, absenteeism is reduced, the workforce is more efficient and most importantly, patients receive better care (NHS Employers, 2019). Aim: The London Hospices LGBT Network was launched in October 2017, following collaboration between nine hospices who marched at London Pride. The network aims to: Promote equality, diversity and inclusion of LGBT people across London hospices; Provide leadership, support and education; Raise awareness of hospice care in LGBT communities. Methods: All London hospices were invited to join the network. The Network launched with a learning event to share the findings from the acclaimed ACCESSCare project (Bristowe, Hodson, Wee, Almack, et al ., 2018), and the Marie Curie survey of hospice staff, 2016. Quarterly network meetings established. Results: Eleven hospices are network members. Nine hospices will march at London Pride in 2019. Hospices in the Midlands and Bristol were inspired to march in their own regional Pride. Newsletter produced and sent to all London hospices. Training planned for November 2019 at Hospice UK. Conclusion: The London Hospices LGBT Network has raised the profile of the LGBT hospice workforce, encouraging visibility, engagement and offering support to those who may be isolated and at risk of marginalisation or discrimination in the workplace. The network believes that acknowledging the difference and contribution that LGBT staff make leads to better outcomes for everyone.